Mining crime instance records of Philippine National Police District Vi âA ¸S˘ Province of Cavite, Philippines: An Exploratory Study to Enhance Crime Prevention Programs - MENGVI P. GATPANDAN; SHANETH C. AMBAT (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This analysis aimed to assess the effectiveness, productivity, and management of one of the country’s national police forces. In this study, especially in the data envelopment analysis, crime management was taken into account as the primary function of the police, which necessitated the use of resources that were viewed as decision-making units.Methodology: To identify productive DMUs, the study combined a Rate-to-Scale (RTS) metric based on scale efficiency with an input-oriented radial measure of efficiency. In the analytical tasks, clustering was used as part of a structured approach to planning data mining activities known as CRISP-DM.Findings: Municipality C is the most efficient DMU based on the 3-year scale efficiency result.Implications/Novelty: Given the current push by the government and the PNP to eradicate criminality and illegal activity in the Philippines, this research couldn’t come at a better time. This research aided police departments and crime scene investigators in identifying patterns of criminal activity and performing geospatial analyses.